An elective course as a way of forming foreign language linguistic competence - Oksana Vladimirovna Khasanova, Oksana Vladimirovna Shemshurenko, Anna Anatolyevna Karimova,; Viktorovna Shustova, Svetlana (Opción, 2019)
This article is devoted to the problem of formation of linguistic competence of students of the Institute of Philology and Intercultural Communication of Kazan Federal University through the elective course fundamentals of Testology in teaching foreign languages as a method. It is experimentally proved that the students who chose the elective course, deepening knowledge in the field of a foreign language, during the semester significantly improved performance in such areas as speaking, vocabulary and grammar, listening, writing and reading. In conclusion, the course Testology can be an effective means of forming the linguistic competence of students of Kazan Federal University.